Pemberian Asuhan Berkelanjutan (Continuity Of Care/ COC) dari Masa Kehamilan sampai Keluarga Berencana pada Ny.L Usia 28 Tahun G1p0a0 di Puskesmas Cilacap Utara 1 - Sujianti, Sujianti; Setyawati, Wilis (Universitas Pahlawan Tuanku Tambusai, 2025)
Efforts to reduce the Maternal Mortality Rate and Infant Mortality Rate in Indonesia by providing Continuity of Care (COC), namely continuous midwifery care provided comprehensively starting from pregnancy, childbirth, newborns, postpartum, to family planning, as well as continuous care according to wishes and is not authoritarian and respects women's choices. Objective: to provide continuous care from pregnancy to family planning to Mrs. L, 28 years old, G1P0A0, at the North Cilacap Community Health Center 1. Method : descriptive research design with a case study approach. Results: Mrs. L, 28 years old, G1P0A0, was pregnant with complications, namely placenta previa at 37 weeks of gestation. The delivery process was carried out by cesarean section due to indications of placenta previa. Postpartum monitoring and the condition of the newborn went well and without complications. The mother chose family planning using intrauterine devices (IUDs) to manage her next pregnancy.